Method for Evaluating the Digital Potential of a Backbone Innovative Active Industrial Cluster - Tashenova, L.; Babkin, A.; Mamrayeva, D.; Babkin, I. (International Journal of Technology, 2020)
Issues of digitalizing industrial enterprises and clusters in the formation of Industry 4.0 garner considerable attention. Here, the discussion is about backbone innovative active industrial enterprises, whose appearance is thanks to the evolutionary development of integrated industrial structures, and which are able to actively create, introduce, and commercialize innovative products and to use all the advantages of industrial automation. The authors attempt to develop a method for assessing the digital potential of backbone innovative active industrial clusters. The method is developed based on existing methods for and approaches to evaluating the innovation potential of industrial clusters and the digital potential of industrial enterprises, and makes it possible to calculate a final integral assessment, which includes calculating for each of the seven sub-potentials the parameters identified by experts to be important. In order to confirm the validity of the obtained results, the calculation is carried out using three methods: arithmetic mean, harmonic mean, and weighted geometric mean. The suggested method was successfully tested on the example cluster “Development of information technologies, radio electronics, instrumentation, communication and info-telecommunication devices of St. Petersburg.“
Keywords: Backbone innovative active industrial cluster; digital economy; digital potential; evaluation method; innovation